Synthesis of an α-phosphono-α,α-difluoroacetamide analogue of the diphosphoinositol pentakisphosphate 5-InsP7 - Riley, A; Wang, H; Shears, S; Potter, B (Royal Society of Chemistry, 2019)
Diphosphoinositol phosphates (PP-InsPs) are an evolutionarily ancient group of signalling molecules that are essential to cellular and organismal homeostasis. As the detailed mechanisms of PP-InsP signalling begin to emerge, synthetic analogues of PP-InsPs containing stabilised mimics of the labile diphosphate group can provide valuable investigational tools. We synthesised 5-PCF2Am-InsP5 (1), a novel fluorinated phosphonate analogue of 5-PP-InsP5, and obtained an X-ray crystal structure of 1 in complex with diphosphoinositol pentakisphosphate kinase 2 (PPIP5K2). 5-PCF2Am-InsP5 binds to the kinase domain of PPIP5K2 in a similar orientation to that of the natural substrate 5-PP-InsP5 and the PCF2Am structure can mimic many aspects of the diphosphate group in 5-PP-InsP5. We propose that 1, the structural and electronic properties of which are in some ways complementary to those of existing phosphonoacetate and methylenebisphosphonate analogues of 5-PP-InsP5, may be a useful addition to the expanding array of chemical tools for the investigation of signalling by PP-InsPs. The PCF2Am group may also deserve attention for wider application as a diphosphate mimic.